Post-induction infliximab trough levels and disease activity in the clinical evolution of pediatric ulcerative colitis. Issue 4 (May 2020) - Moore, Hillary; Dolce, Pasquale; Devas, Nina; Baldassano, Robert; Martinelli, Massimo
Background and aims: Recent adult evidence suggests that infliximab (IFX) trough levels (TL) in patients with severe ulcerative colitis (UC) may be decreased. The aims of our study were to compare post-induction IFX TL of children with severe versus moderate UC and to evaluate short- and long-term outcomes. Methods: In this single-center retrospective study, children with a diagnosis of UC starting IFX with a Pediatric Ulcerative Colitis Activity Index (PUCAI) ≥35 and with available post-induction TL were recruited. UC characteristics, IFX dosage and interval, primary non-response, IFX failure, and surgery after 24 months were collected. Post induction TL, anti-IFX antibodies, and laboratory evaluations at the time of starting IFX were also acquired. Results: A total of 90 children were enrolled, of whom 39 (43.3%) were classified as severe UC and 51 (56.6%) as moderate UC. Median post-induction IFX TL were lower in severe UC versus moderate group (5.5 vs 10.3; p  = 0.03), despite a more frequently intensified IFX regimen. Children in the higher TL quartiles showed increased rates of clinical, biological, and combined remission ( p  = 0.04, p  < 0.001, and p  = 0.01, respectively). In a multivariate analysis, a PUCAI ≥65 and time interval from last IFX infusion were the only predictors associated with IFX TL. At 24 months, children in the higher TL quartiles had a decreased risk of IFX failure ( p  = 0.002). The severe UC group showed a higher risk of IFX failure at 24 months (16/23 (41%) vs. 11/40 (21.6%); p  = 0.05). Kaplan–Meier methods demonstrated a trend toward statistical significance, with a two-year cumulative colectomy rate of 15.38% (95% confidence interval (CI) 8.1–15.6%) in children with severe UC and 3.92% (95% CI 2.9–10.8%) in patients with moderate UC (logrank test p  = 0.06). Conclusions: Children starting IFX with severe UC showed lower post-induction TL and poor disease outcomes. Achieving adequate TL was associated with better efficacy outcomes.